Team Assisted Individualization: Efektivitas Model Pembelajaran Cooperative Terhadap Minat Belajar Peserta Didik - Pitra Gosha Patriasya Nurul; Hauzzan Felgiansyah; Intan Indah Maharany; Endhah Tryadumawati; Jeny Almira; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
The low interest and academic performance of students are often caused by the use of conventional teaching methods, differences in student backgrounds, low motivation, and a lack of flexibility in the learning process. This study aims to examine the effect of the Team Assisted Individualization (TAI) learning model on students' interest in Islamic Religious Education at SMP Negeri 23 Bandar Lampung. A quantitative approach was employed using a quasi-experimental design. The research population consisted of 250 eighth-grade students, with the sample selected randomly using the Spin the Wheel application. Class VIII F was designated as the experimental group, while Class VIII E served as the control group. Data were collected through a post-test questionnaire and analyzed using normality, homogeneity, and t-tests. The results showed that students who participated in learning through the TAI model demonstrated a higher level of interest compared to those who experienced conventional learning. This was evidenced by a significance value of 0.000 < 0.05. These findings indicate that the TAI learning model is effective in enhancing students’ learning interest. Therefore, it is recommended that teachers begin implementing models such as TAI to create a more engaging and collaborative learning environment, which can ultimately have a positive impact on overall academic achievement.